A COMPARISON OF CONSERVATION TECHNOLOGIES AND TRADITIONAL TECHNIQUES FOR SOWING OF WHEAT - M. H. Kahloon; M. F. Iqbal; M. Farooq; Liaqat Ali; M. Fiaz; I. Ahmad Adaptive Research Farm; Gujranwala-Pakistan Pest Warning & QCP; Gujranwala; Pest Warning & QCP; Multan; Pest Warning & QCP; Punjab; et al. (Journal of Animal and Plant Sciences, 2012)
The conservation technologies and traditional techniques were evaluated at Adaptive  Research Farm Gujranwala Pakistan during Rabi 2007-2008 and 2008-2009. The sowing techniques evaluated were broadcasting (T-1), Rotary Tillage Drill (T-2), Zero Tillage Drill (T-3) and Rabi Drill (T-4). Rotary Tillage Drill showed significantly high germination count (220.50 m-2) followed by Rabi Drill (211.50 m-2), Zero Tillage Drill (195.34 m-2) and broadcasting (182.84 m-2), respectively. Rotary Tillage Drill (T-2) produced maximum number of grains spike-1 (52.61) which was significantly high as compared to Rabi Drill (48.11), zero tillage drill (45.55) and broadcasting (41.77). Similarly Rotary Tillage Drill produced highly significant effect on grain yield (4.71t ha-1) as compared to other treatments i.e. 3.75, 3.04 and 2.61 t ha-1 in case of Rabi Drill, Zero Tillage Drill and broadcasting, respectively. Rotary tillage drill (T-2) gave maximum net income (Rs.36442 ha-1) with a CBR of 1:12.80 compared with rabi drill (T-3) net income Rs. 15892 ha-1 with CBR 1:6.80 and zero tillage (T-4) i.e. Rs.8610 ha-1 with CBR 1:5.00 over broadcasting method.
Keywords: Conservation Technologies; Broadcasting; save time; energy; CBR; Pakistan